“Caminando Con Riesgo”: perceptions of occupational injury, workplace safety and workers rights among Spanish-speaking hospitalized patients - Zeidan, Amy; Cortes, Juliana; Marcovitch, Hannah; Chicas, Roxana; Smith, Randi N.; Stevens, Alessandra; Zambrana, Elizabeth; Anand, Shelly (Frontiers in Public Health, 2024)
Introduction Occupational health disparities are well documented among immigrant populations and occupational injury remains a high cause of morbidity and mortality among immigrant populations. There are several factors that contribute to the high prevalence of work-related injury among this population and those without legal status are more likely to experience abusive labor practices that can lead to injury. While the work-related injuries and experiences of Spanish-speaking workers have been explored previously, there is a paucity of literature documenting injury among hospitalized patients. Additionally, there are few documented hospital-based occupational injury prevention programs and no programs that implement workers rights information. The purpose of this study was to further explore the context of work related injuries primarily experienced by Spanish speaking patients and knowledge of their rights in the workplace. Methods This was a semi-structured qualitative interview study with Spanish speaking patients admitted to the hospital for work related injuries. The study team member conducting interviews was bilingual and trained in qualitative methodology. An interview guide was utilized for all interviews and was developed with an immigrant workers rights organization and study team expertise, and factors documented in the literature. Participants were asked about the type and context of the injury sustained, access and perceptions of workplace safety, and knowledge of participants rights as workers. All interviews were conducted in Spanish, recorded, transcribed in Spanish and then translated into English. A codebook was developed and refined iteratively and two independent coders coded all English transcripts using Dedoose. Interviews were conducted until thematic saturation was reached and data was analyzed using a thematic analysis approach. Results A total of eight interviews were completed. All participants reported working in hazardous conditions that resulted in an injury. Participants expressed a relative acceptance that their workplace environment was dangerous and acknowledged that injuries were common, essentially normalizing the risk of injury. There were varying reports of access to and utilization of safety information and equipment and employer engagement in safety was perceived as a facilitator to safety. Most participants did have some familiarity with Occupational Safety and Health Administration (OSHA) inspections but were not as familiar with OSHA procedures and their rights as workers. Discussion We identified several themes related to workplace injury among Spanish speaking patients, many of which raise concerns about access to workplace safety, re-injury and long-term recovery. The context around immigration is particularly important to consider and may lead to unique risk factors for injury, recovery, and re-injury both in the workplace and beyond the workplace, suggesting that perhaps immigration status alone may serve as a predisposition to injury. Thus, it is critical to understand the context around work related injuries in this population considering the tremendous impact of employment on one’s health and financial stability. Further research on this topic is warranted, specifically the exploration of multiple intersecting layers of exposure to injury among immigrant populations. Future work should focus on hospital-based strategies for injury prevention and know your rights education tailored to Spanish speaking populations.